Water Quality Monitoring for Trophic State of Tasik Kemajuan, Universiti Tun Hussein Onn Malaysia - Azman, Muhammad Hafiq Afifi; Hamdan, Rafidah; Md Ali, Zarina; Siddiqui, Zuhaib (International Journal of Sustainable Construction Engineering and Technology, 2023)
Aquatic ecosystems offer several ecosystem services, including water purification, nutrient recycling, flood reduction, groundwater recharge, irrigation, and animal habitats. One of the most prevalent challenges freshwater systems face globally is eutrophication. Eutrophication refers to the process of increasing the concentration of plant nutrients in water. The Carlson’s Trophic State Index (CTSI) categorises an aquatic environment’s eutrophication condition. The parameters exclusively employ three water quality parameters, which are Secchi Disc Transparency (SD), Total Phosphorus (TP), and Chlorophyll-a (Chl-a). Biological indicators refer to living organisms, such as plants and macroinvertebrates, that are implemented to identify and assess the presence of pollutants within a specific ecosystem. Therefore, this study focuses on the determination of trophic state and the assessment of biological indicators of Tasik Kemajuan. Water samples were collected for nine weeks using the composite sampling method for laboratory analysis. Water transparency was determined using a Secchi Disc. The Chl-a was determined by using the determination of chlorophyll-a using 90% methanol and measuring the absorption using a Hach DR6000 UV VIS Spectrophotometer at 663 nm and 750 nm, while the Total Phosphorus was determined by using USEPA1 PhosVer® 3 with Acid Persulfate Digestion Method (Method 8190). Tasik Kemajuan exhibited eutrophic conditions over the duration of the nine-week period. The CTSI values exhibited a range of 60 to 80, thereby demonstrating that the water body under consideration is in a state of eutrophication. The Red Claw Crawfish (Cherax Quadricarinatus), Amona Prawn (Caridina Multidentata), Freshwater Snail (Viviparidae), Tiger Barb (Puntius Tetrazona), and Waterlily (Nymphaeaceae) are among the biological indicators found in Tasik Kemajuan. In conclusion, the analysis of the result shows that the Tasik Kemajuan is in an eutrophic condition, which has high amounts of algae growth, and the bottom waters are seriously depleted in oxygen.